Minat Pedagang Muslim Menabung Di Perbankan Syariah: Seberapa Besar Pengaruh Pengetahun dan Budaya Kerja? - sakum, sakum; Ainulyaqin, MH; Achmad, Listian I.; Mamun, Sukron; Anggadita, Intan (ITB AAS INDONESIA Surakarta, 2024)
The purpose of this study was to determine the effect of the level of knowledge and work culture on the interest of Muslim traders to save in Islamic banking. The research method used in this study uses a quantitative approach, namely by filling out a questionnaire as a data collection tool. Measurement of data was carried out using a Likert scale and processed using the help of the SPSS IBM 24 application. The sample in this study was the Islamic book marketer Najah Bookstore as many as 67 respondents. The results of this study indicate that there is an influence between knowledge and interest in saving of 2,517 and the influence of work culture on interest in saving is 7,984. Meanwhile, simultaneously, knowledge and work culture have an effect of 135,142. And based on the results of the determinant coefficient test, it is known that knowledge and work culture have an effect of 80.9% on the interest of Muslim traders to save in Islamic banking.